Judge Freedom Versus Accountability on Oversight System and Ethics Enforcement Mechanism in Criminal Justice in Indonesia - Pramono, Gunadi; Hidayatullah, Hidayatullah; Munawar, Akhmad (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This study examines the delicate balance between judicial independence and accountability within Indonesia's criminal justice system, focusing on mechanisms of oversight and ethical enforcement. Judicial independence serves as a fundamental pillar in ensuring impartial court decisions; however, it necessitates a robust accountability system to prevent abuses of power and maintain public trust. Using a normative juridical method, this research analyzes the legal framework governing judicial oversight and ethics enforcement mechanisms. Findings suggest that while Indonesia has established institutions such as the Judicial Commission and the Supreme Court to oversee judicial conduct, their coordination remains suboptimal. The lack of enforcement power for the Judicial Commission often results in ethical violations not being adequately addressed. Additionally, judges frequently face external pressures, particularly in high-profile cases, which may compromise their independence. This study highlights key challenges, including structural limitations in the supervisory system, public and media influence on judicial decision-making, and insufficient transparency in ethical oversight. To strengthen judicial integrity, the research recommends enhancing the authority of the Judicial Commission, improving inter-institutional coordination, and increasing transparency in judicial accountability processes. These findings contribute to the ongoing discourse on legal reform in Indonesia and propose strategies to ensure a fairer and more accountable judiciary.